2005
DOI: 10.1074/jbc.m412118200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic Analyses of Arginine Residues in the Active Site of the Acetate Kinase from Methanosarcina thermophila

Abstract: Phosphoryl transfer is a key reaction in numerous biological processes, playing roles in signaling mechanisms, energy transfer, and energy storage in both eukaryotic and prokaryotic cells (1). One of the earliest phosphoryl transfers identified was the phosphorylation of acetate by ATP to form acetyl phosphate (AcP) 1 and ADP, described in 1944 by Lippman (2). This reversible reaction is catalyzed by acetate kinase, which is widely distributed among anaerobic prokaryotes playing a central role in energy-yieldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
95
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(110 citation statements)
references
References 57 publications
15
95
0
Order By: Relevance
“…As expected, this experiment demonstrates that the enzyme follows standard Michaelis-Menten-like kinetics for each substrate and produced a hyperbolic saturation curve when plotting activity versus acetyl phosphate concentration. The apparent Km value for acetyl phosphate was 0.27 ± 0.01 mmol/L, which compares favorably to the published Km value of 0.47 ± 0.01 mmol/L using the coupled assay 13 .…”
Section: Representative Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…As expected, this experiment demonstrates that the enzyme follows standard Michaelis-Menten-like kinetics for each substrate and produced a hyperbolic saturation curve when plotting activity versus acetyl phosphate concentration. The apparent Km value for acetyl phosphate was 0.27 ± 0.01 mmol/L, which compares favorably to the published Km value of 0.47 ± 0.01 mmol/L using the coupled assay 13 .…”
Section: Representative Resultssupporting
confidence: 72%
“…Acetate kinases are ubiquitous in the Bacteria, found in one genus of Archaea, and are also present in microbes of the Eukarya 6 . The most well characterized acetate kinase is that from the methane-producing archaeon Methanosarcina thermophila [7][8][9][10][11][12][13][14] . An acetate kinase which can only utilize PPi but not ATP in the acetyl phosphate-forming direction has been isolated from Entamoeba histolytica, the causative agent of amoebic dysentery, and has thus far only been found in this genus 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent crystal structure of the M. thermophila acetate kinase containing acetate, ADP, and the transition state analog AlF 3 further supported the hypothesis that there is a direct in-line mechanism and showed the methyl group of acetate located in the previously proposed binding pocket (14). Kinetic analyses of active site replacement variants also supported the hypothesis that there is a direct in-line mechanism for the M. thermophila enzyme and suggested roles for conserved arginine, histidine, and glutamate residues (16,26,27,32,33).…”
mentioning
confidence: 63%
“…Located in the M. thermophila acetate kinase active site cleft are the residues Val 93 , Phe 179 , and Pro 232 , which form a hydrophobic pocket ( Fig. 1) predicted to bind the methyl group of acetate (8,14). Sequence alignments (data not shown) revealed that Val 93 , Phe 179 , and Pro 232 of the M. thermophila enzyme are strictly conserved in all other acetate kinases obtained from the databases, implying that these residues have important roles, possibly in substrate binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation